2020
DOI: 10.1016/j.kint.2019.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Calciprotein particles regulate fibroblast growth factor-23 expression in osteoblasts

Abstract: hosphorus homeostasis at the organismal level is maintained by balancing phosphate intake and excretion. Specifically, the amount of phosphate excreted into urine is regulated so as to become equal to the amount of phosphate absorbed from the digestive tract. 1 The amount of urinary phosphate excretion is primarily regulated by the endocrine axis consisting of fibroblast growth factor-23 (FGF23) and its obligate coreceptor klotho. FGF23 is a hormone secreted from osteoblasts and osteocytes in response to phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
88
1
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(97 citation statements)
references
References 25 publications
4
88
1
4
Order By: Relevance
“…A study in rats showed that increased Fgf23 transcription in response to high dietary phosphate is only possible when serum calcium levels are also high (84). This is in agreement with another study showing that it is not the increase of phosphate itself that increases Fgf23 transcription, but rather the formation of calciprotein particles (CCPs) (85). CCPs are colloidal nanoparticles that consist of calcium and phosphate circulating in the blood and are potentially harmful as they contribute to vascular calcification.…”
Section: Calciumsupporting
confidence: 68%
“…A study in rats showed that increased Fgf23 transcription in response to high dietary phosphate is only possible when serum calcium levels are also high (84). This is in agreement with another study showing that it is not the increase of phosphate itself that increases Fgf23 transcription, but rather the formation of calciprotein particles (CCPs) (85). CCPs are colloidal nanoparticles that consist of calcium and phosphate circulating in the blood and are potentially harmful as they contribute to vascular calcification.…”
Section: Calciumsupporting
confidence: 68%
“…Next, we incubated the mixture for 24 h at 37 °C and then centrifuged it at 16,000 × g for 2 h. After removing the supernatant, we suspended the precipitated CPPs with the same amount (25 mL) of DMEM/F-12 containing 10% FBS to make 1 × CPP, or one-fifth of the initial amount (5 mL), to make 5 × CPP. The total calcium and phosphorus content in 1 × CPP was determined by ICP-MS Nexion 2000 as previously described 54 . 1 × CPP contained 174.8 μg calcium/mL (4.36 mM) with the standard error of mean ± 3.0 and 105.2 μg phosphorus/mL (3.40 mM) with the standard error of mean ± 2.9.…”
Section: Cpp Preparationmentioning
confidence: 99%
“…And most recently, Akiyama et al determined the hydrodynamic radii of CPPs in cell culture by small angle X-ray scattering (SAXS), from which they derived the size and shape of CPPs [19]. However, it remains a challenging task to acquire direct structural information of the protein-bound calcium phosphate, owing to the crystallizing propensity of the calcium phosphate clusters and amorphous phase.…”
Section: Introductionmentioning
confidence: 99%